Intelligence Networks – The Model Based Methodologies Problem - Berbec, Mihaela (Calitatea Vieții, 2009)
Social innovation requires research regarding the profit potential of human interaction, in various settings and information environments. Throughout networking processes, the added value of information, together with organizational skills and methods brought into the system helps render a more efficient governance control of the national security systems. Previous studies showed the influence of social networks on political and business systems (Carley, 2002) as well as the need to create intelligent social structures, in order to foster innovation and competitive advantage (Steele, 2001). This paper examines the intelligence network concept and methodological issues contained in the structure design processes.